Unraveling ScAPD1-mediated resistance mechanism to Verticillium dahliae through integrated host-pathogen transcriptomics - Qilin Yang; Ruirui Yang; Huan Zhang; Fangliu Yin; Leyi Wang; Daoyuan Zhang; Xiaoshuang Li (Plant Stress, 2025)
Verticillium dahliae, a devastating vascular wilt pathogen, poses a significant threat to global agriculture. Understanding host resistance mechanisms is critical for developing effective control strategies. This study investigates the role of ScAPD1, a Soloist transcription factor from the extremophilic moss Syntrichia caninervis, in conferring resistance to V. dahliae when overexpressed in the model plant Arabidopsis thaliana. We employed an integrated host-pathogen transcriptomics approach (dual RNA-seq), alongside physiological and biochemical experiments. Phenotypic analysis confirmed enhanced resistance in transgenic A. thaliana overexpressing ScAPD1 (SC lines), characterized by attenuated disease symptoms and significantly reduced fungal biomass. Transcriptomic analysis revealed a striking divergence in host response: while V. dahliae infection severely suppressed photosynthesis-related pathways in wild-type (WT) plants, SC lines maintained their photosynthetic capacity; this preservation of primary metabolism indicates a key component of ScAPD1-mediated resistance. EMSAs demonstrated that ScAPD1 directly binds to promoter regions of key photosynthesis genes PsbQ1 and PsbO1, providing a direct mechanistic link to this preserved primary metabolism. Concurrently, SC lines exhibited enhanced activation of defense-related pathways, including flavonoid biosynthesis. V. dahliae infecting SC lines displayed widespread suppression of genes involved in essential metabolic processes (e.g., ribosome biogenesis) and putative virulence factors, particularly at later infection stages. These findings indicate that ScAPD1 plays a central role in plant resistance to V. dahliae by implementing a potent, two-pronged strategy: it directly regulates and stabilizes host photosynthetic integrity to support sustained defense responses, while simultaneously creating an unfavorable intracellular environment that hinders pathogen metabolic adaptation and virulence. By revealing this sophisticated, dual regulatory mechanism, this study establishes the unique, moss-derived ScAPD1 as an exceptionally valuable candidate gene for engineering robust Verticillium wilt resistance.